Faculty development on professionalism and medical ethics: The design, development and implementation of Objective Structured Teaching Exercises (OSTEs). (October 2014) - Lu, Wei-Hsin; Mylona, Elza; Lane, Susan; Wertheim, William A.; Baldelli, Perrilynn; Williams, Peter C.
Abstract Background: As students are expected to develop competency in professionalism and medical ethics, faculty are also expected to facilitate medical students' learning and understanding of these areas. One of the main challenges to success in this domain has been uncertainty of whether or not faculty know the content and the methods to teach and assess these competencies. Aim: We used the Objective Structured Teaching Exercise (OSTE) format as a faculty development tool to train and evaluate faculty on how to teach professionalism and medical ethics to students in clinical settings. Methods: The process for the design, development and implementation of OSTEs consisted of five phases: (1) performing a literature review and student needs assessment, (2) developing the OSTE cases and performance checklists, (3) recruiting and training of standardized students, (4) conducting a mock training session and (5) organizing faculty development workshops using OSTEs. Results: Twenty clinical faculty members participated in one of three half-day OSTE workshops offered. Faculty confidence and attitudes about teaching professionalism increased significantly (p < 0.05) from before participating in the workshop to afterwards. Conclusions: Faculty feedback were positive stating that the OSTE scenarios were reflective of issues they generally encounter while teaching medical students, the information and skills they learned from the workshop are important to them as clinical educators, and that the information and skills will likely have an impact on the way they teach professionalism and ethics in the future.